Amplatzer atrial septal defect occluder device embolisation to right pulmonary artery - Khakural, Prabhat; Baral, Ravi; Bhattarai, Anil; Koirala, Bhagawan (Journal of Kathmandu Medical College, 2022)
Atrial septal defect is a common congenital acyanotic heart disease which is treated with either surgical closure or transcatheter closure. Although surgical closure is gold standard, transcatheter device closure is gaining popularity worldwide and in Nepal due to favourable outcome in selected patients. Device migration following transvenous closure of atrial septal defect is a common problem but its lodgment in right pulmonary artery is a rarely encountered and reported clinical scenario. Here, the authors report a case of 42-year-old female who had an embolisation of Amplatzer septal occluder to right pulmonary artery requiring urgent surgical intervention to retrieve the device.